Canopy light distribution effects on light use efficiency in wheat and its mechanism - Zhang, Jie; Zhang, Zhiyong; Neng, Furong; Xiong, Shuping; Wei, Yihao; Cao, Rui; Wei, Qiongru; Ma, Xinming; Wang, Xiaochun (Frontiers in Ecology and Evolution, 2022)
Optimizing canopy light distribution (CLD) has manifested improved light utility and yield without modifying other inputs. Nonetheless, molecular mechanisms working at cellular and organelle level remain to be elucidated. The current study aimed to assess the effect of CLD on photosynthetic performance and yield of wheat, and to investigate into the molecular mechanism underlying the photosynthetically active radiation (PAR) - use efficiency (PUE) at optimized CLD. Wheat was planted in two rows having different spacing [R1 (15 cm) and R2 (25 cm)] to simulate different CLD. Flag and penultimate leaves were subjected to chloroplast proteomics analysis. An increase in row spacing positively affects CLD. A decrease (16.64%) of PAR interception in the upper layer, an increase (19.76%) in the middle layer, improved PUE (12.08%) and increased yield (9.38%) were recorded. The abundance of proteins associated with photosynthetic electron transport, redox state, and carbon-nitrogen assimilation was differentially altered by CLD optimization. In the penultimate leaves, R2 reduced the abundance of PSII light-harvesting proteins, PSII-subunits, and increased the PSI light-harvesting proteins, NAD(P)H quinone oxidoreductase and enzymes involved in carbon assimilation compared to R1. Additionally, leaf stomatal conductance increased. Altogether, These these findings demonstrated that the regulation of chloroplast proteome is intimately linked to light utilization, which provide basis for genetic manipulation of crop species for better adaptation and improving PUE andimprovement of cultivation strategies.